Fluoride Adsorption by Pumice from Aqueous Solutions - Amir Hossein Mahvi; Behzad Heibati; Alireza Mesdaghinia; Ahmad Reza Yari (E-Journal of Chemistry, 2012)
Drinking water provides many vital elements for the human body, but the presence of some dissolved elements more than permissible concentration can endanger human health. Among the dissolved elements in drinking water, fluoride is noticeable, because both the very low or very high concentrations have adverse health impacts such as dental caries. Therefore, fluoride concentration should be kept in acceptable levels. In this study Pumice was used for fluoride removal. It was found that Fluoride sorption kinetic was fitted by pseudo-second-order model. The maximum sorption capacity of Pumice was found to be 13.51 mg/g at laboratory temperature (24°C). Maximum sorption study occurred at pH= 3. Results of Isotherm showed the fluoride sorption has been well fitted with Freundlich isotherm model. This study has demonstrated that Pumice can be used as effective adsorbents for fluoride removal from aqueous solutions. The adsorbent prepared in this study was cheap and efficient in removal of fluoride than other adsorbents.